Investigating the quality of marketed Azithromycin in the Democratic Republic of the Congo: A case of tablets in the city of Kisangani - Ngwato, Jean-Willy; Mankulu Kakumba, Jocelyn; Mayangi Makola, Mannix; Ntambwe Ngoyi, Michel; Mufusama Koy Sita, Jean-Pierre; Liesse Iyamba, Jean-Marie; Ciza Hamuli, Patient (Orapuh Journal, 2025)
IntroductionAzithromycin is an antibiotic belonging to the macrolide family. It is widely used in the management of infectious diseases caused by both Gram-positive and Gram-negative bacteria, as well as certain aerobic infections. During the COVID-19 outbreak, its use increased in many countries as part of disease management protocols. Unfortunately, this surge was associated with the introduction of counterfeit products on the market. This drug remains widely circulated, particularly in the far north of Kisangani Province in the Democratic Republic of the Congo.PurposeThis study aimed to evaluate the quality of marketed Azithromycin tablets available in the region of Kisangani, Democratic Republic of the Congo.MethodsTo achieve this goal, appropriate physicochemical analyses were conducted to verify product quality through organoleptic, pharmaco-technical, qualitative, and quantitative assessments. A total of 14 samples from seven different laboratories (two batches from each) were collected. The study adopted a cross-sectional laboratory-based design using UV-Vis spectrophotometry and HPLC techniques. Data were statistically analysed using the Student’s t-test method.ResultsAnalyses yielded satisfactory results for 100% of the samples, which were consistent with survey findings and confirmed the effectiveness and reliability of Azithromycin-based treatment, except for one sample (Zithromcin, batches 1 and 2) that failed the friability test. This non-conforming result represented less than 20% of the total sample size.ConclusionThe study results align with those obtained from the survey. We recommend that regulatory authorities use similar analytical tests and trials for drug approval processes and the classification of high-monitoring drugs. The analytical methods implemented in this research can serve as reference procedures for routine quality control of this macrolide antibiotic.